Rutin Inhibits Streptococcus suis Biofilm Formation by Affecting CPS Biosynthesis - Wang, Shuai; Wang, Chang; Gao, Lingfei; Cai, Hua; Zhou, Yonghui; Yang, Yanbei; Xu, Changgeng; Ding, Wenya; Chen, Jianqing; Muhammad, Ishfaq; Chen, Xueying; He, Xinmiao; et al. (Frontiers in Pharmacology, 2017)
Streptococcus suis (S. suis) form biofilms and causes severe diseases in humans and pigs. Biofilms are communities of microbes embedded in a matrix of extracellular polymeric substances. Eradicating biofilms with the use of antibiotics or biocides is often ineffective and needs replacement with other potential agents. Compared to conventional agents, promising and potential alternatives are biofilm-inhibiting compounds without impairing growth. Here, we screened a S. suis adhesion inhibitor, rutin, derived from Syringa. Rutin, a kind of flavonoids, shows efficient biofilm inhibition of S. suis without impairing its growth. Capsular polysaccharides(CPS) are reported to be involved in its adherence to influence bacterial biofilm formation. We investigated the effect of rutin on S. suis CPS content and structure. The results showed that rutin was beneficial to improve the CPS content of S. suis without changing its structure. We further provided evidence that rutin specifically affected S. suis biofilm susceptibility by affecting CPS biosynthesis in vitro. The study explores the antibiofilm potential of rutin against S. suis which can be used as an adhesion inhibitor for the prevention of S. suis biofilm-related infections. Nevertheless, rutin could be used as a novel natural inhibitor of biolfilm and its molecular mechanism provide basis for its pharmacological and clinical applications.